Crop Improvement from Phenotyping Roots: Highlights Reveal Expanding Opportunities - Tracy, Saoirse R.; Nagel, Kerstin A.; Postma, Johannes A.; Fassbender, Heike; Wasson, Anton; Watt, Michelle (Trends in plant science, 2020)
Root systems determine the water and nutrients for photosynthesis and harvested products, underpinning agricultural productivity. We highlight 11 programs that integrated root traits into germplasm for breeding, relying on phenotyping. Progress was successful but slow. Today’s phenotyping technologies will speed up root trait improvement. They combine multiple new alleles in germplasm for target environments, in parallel. Roots and shoots are detected simultaneously and nondestructively, seed to seed measures are automated, and field and laboratory technologies are increasingly linked. Available simulation models can aid all phenotyping decisions. This century will see a shift from single root traits to rhizosphere selections that can be managed dynamically on farms and a shift to phenotype-based improvement to accommodate the dynamic complexity of whole crop systems. Root and rhizosphere traits have been selected and incorporated into germplasm since the 1970s, proving the value of roots and phenotyping in prebreeding programs.Past examples show how today’s noninvasive phenotyping technologies that measure roots, shoots, and seeds, can be strategically combined to speed up germplasm enhancement.Models are available to test and incorporate root phenotypes at different stages of selection programs.The root–soil rhizosphere can be phenotyped noninvasively in soils, revealing new combinatorial traits relevant to the reality of farming systems and to select for crop improvement.